Tetrastigma hemsleyanum as a feed additive: modulating gut microbiota for enhancing nutritional transport and growth performance in Jinhua yellow chickens - Chao Lu; Yun Xiang; Kewei Xu; Fengrui Gao; Shaofeng Zhu; Fangfang Lou; Lu Liu; Xin Peng (Poultry Science)
Tetrastigma hemsleyanum (TH) has attracted much attention for its heat clearing and detoxification effects, but whether it can become an effective feed supplement in chickens remains unclear. Herein, a total of 120 male Jinhua yellow chickens (two-mth-old) were randomly divided into into four groups (CON, TH-L, TH-M, and TH-H) for a 56-day feeding trial to explore its effects on growth performance and underlying mechanism. Results revealed that dietary TH notably increased the average daily growth (ADG), and decreased the average daily feed intake (ADFI) and feed conversion ratio (FCR) in TH-H group during 29-56 days. Meanwhile, dietary TH improved the development of duodenum and notably increased the contents of essential amino acids and flavor amino acids, while the serum oxidation stress index as well as abdominal fat deposition were not affected in Jinhua yellow chickens. Additionally, TH supplementation notably increased gut microbiota richness, then selectively increased the colonization of potential probiotics and the microbial abundance associated to amino acid synthesis and metabolic pathways in duodenum. Furthermore, qPCR analysis results preliminarily verified that dietary TH not only enhanced intestinal amino acids (rBAT and EAAT3) and peptides (PepT1 and APN) transport but also alleviated the inflammation (IL-1β, IL-6 and IFN-γ), thus thereby improved intestinal development and growth performance in Jinhua yellow chickens. These findings demonstrated that TH is a feed additive that can improve growth performance, muscle amino acids composition and intestinal development.